Drone-based vertical delivery system for high-rise buildings: Multiple drones vs. a single elevator - Takahiro Ezaki; Kazuhiro Fujitsuka; Naoto Imura; Katsuhiro Nishinari (Communications in Transportation Research)
As urbanization and high-rise living increase, frequent delivery of goods in the building to higher floors from the ground level is becoming a pressing issue. We introduce a drone-based vertical delivery system aimed at enhancing the efficiency of high-rise building logistics. The potential of the proposed system in reducing delivery time and energy consumption compared to conventional elevator-based delivery is analyzed. By assessing the requisite number of drones, their operating frequencies, and identifying scenarios in which drones can surpass conventional methods, the advantages using drone delivery systems are highlighted. The results indicate that drone delivery is not only viable but also advantageous to meet certain demand levels, offering a promising alternative to elevator-based deliveries.